Reappraisal of Prevailing Premises in Sarcoidosis - Reich, Jerome M. (Cambridge Scholars Publishing, 2020)
This book advances an evidence-based, unifying conceptual view of sarcoidosis that accounts for many of its baffling and seemingly paradoxical features. It thoroughly explores certain aspects of sarcoidosis--including its fundamental nature, causation, relationship to neoplasia, and appropriate treatment--in which prevailing premises either lack support or are opposed by a critical analysis of available data. Where possible, the text transcends description by positing plausible pathogenetic mechanisms. The final chapter sketches 20 fundamental questions, suitable candidates for future investig